Tendencies on the issue “ethics in health” in scientific production - Kelly Barros Marques; Simone de Sousa Paiva; Marli Teresinha Gimenez Galvão (Rev Rene)
The existing complexity in the health area makes it difficult for the professional to take a decision before certain situations which makes it necessary to run over certain existing ethic aspects. this research aims to identify scientific articles published on the issue "ethics in health". it is a descriptive, exploratory and bibliographical study for the accomplishment of which 30 articles published between the years 1995 to 2004 and available in the scielo were selected. the following data were considered regarding such studies: year of publication, journal title, type and approach of the study, and the themes of the articles. Na increase in the number of publications on this topic was observed, partly due to the biotechnological advances. however, there was a predominance of publications in public health journals since ethics discusses the collective well-being. Theoreticalreflexive studies were the type which was most frequently found since the theme considered requires critical thought. The conclusion was that a discussion on health ethics requires legal, moral as well as scientific foundations in order to insure the well-being not only of individuals but also of the society in general.